1998
DOI: 10.1002/lt.500040415
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine stress echocardiography for preoperative cardiac risk stratification in patients undergoing orthotopic liver transplantation

Abstract: This study attempts to evaluate the efficacy of dobutamine stress echocardiography for preoperative cardiac risk stratification in patients undergoing orthotopic liver transplantation. Two hundred twenty consecutively submitted patients were evaluated in preparation for orthotopic liver transplantation. Dobutamine stress echocardiography was performed in 80 patients with known or suspected coronary artery disease. Follow-up information was available in 40 patients in the form of cardiac catheterization and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 12 publications
(13 reference statements)
4
88
0
2
Order By: Relevance
“…Results with dobutamine stress echocardiography have shown poor sensitivity and low negative predictive value, partially because of an inability to reach target heart rate. 2,12,13 Most of these patients are on b blockers to decrease portal hypertension and prevent esophageal bleeding. Ideally, a noninvasive test should be highly sensitive to diagnose CAD in potential transplantation patients, considering the perioperative cardiovascular complication risks involved with the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Results with dobutamine stress echocardiography have shown poor sensitivity and low negative predictive value, partially because of an inability to reach target heart rate. 2,12,13 Most of these patients are on b blockers to decrease portal hypertension and prevent esophageal bleeding. Ideally, a noninvasive test should be highly sensitive to diagnose CAD in potential transplantation patients, considering the perioperative cardiovascular complication risks involved with the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Morris et al 16 found that 5.6% of 608 patients aged older than 40 years undergoing OLT had documented CAD, although the diagnostic criteria were not explicitly stated. Plotkin et al, 17 using data from both cardiac catheterization and dobutamine stress echocardiogram (DSE), documented significant CAD, defined as 70% or greater stenosis within a major coronary artery, in 2 of 40 patients (5%) who underwent OLT. In another report evaluating the role of DSE in screening patients with cirrhosis for CAD, Donovan et al 18 found that 2.5% of 165 patients had CAD, defined as greater than 50% coronary artery stenosis on cardiac catheterization.…”
Section: Prevalence Of Cad In Patients With Esldmentioning
confidence: 99%
“…However, based on data from the 4 studies cited, the prevalence rate ranged from 2.5% to 27% (Table 2). [15][16][17][18] Given a 2.5% prevalence rate of CAD in asymptomatic men in the general population, 19 the former belief that CAD was uncommon in patients with cirrhosis no longer appears to be true. The prevalence rate of CAD in ESLD is at least the same and probably greater than in the general population.…”
Section: Prevalence Of Cad In Patients With Esldmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Liver Transplantation and Surgery, Plotkin suggests that I use a diagnostic tool that already has proven efficacy in the general population of patients. 4 In applying this tool, he suggests that I use clinical predictors of CAD that are similar to those suggested by the American College of Cardiology and the American Heart Association. Should we approach the liver transplant candidate in the same fashion as a noncirrhotic patient before some other high risk surgical procedure?…”
mentioning
confidence: 99%